Species and space: a combined gap analysis to guide management planning of conservation areas - Ahmadi, M; Farhadinia, MS; Cushman, SA; Hemami, M-R; Nezami Balouchi, B; Jowkar, H; Macdonald, DW (Springer, 2020)
Context With accelerating global declines in biodiversity, establishment and expansion of conservation areas (CAs) have increasingly been advocated in recent decades. Gap analysis has been useful to evaluate the sufficiency and performance of CAs.